2018
DOI: 10.1155/2018/8271313
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 18F-NaF PET/CT and 18F-FDG PET/CT for Detection of Skull-Base Invasion and Osseous Metastases in Nasopharyngeal Carcinoma

Abstract: Our study aimed at comparing the diagnostic value of 18F-NaF positron emission tomography-computed tomography (PET/CT) and 18F-fluorodeoxyglucose (FDG) PET/CT for detection of skull-base invasion and osseous metastases in patients with nasopharyngeal carcinoma (NPC). Our study retrospectively analyzed 45 patients with pathologically proven NPC. They all underwent both 18F-NaF PET/CT and 18F-FDG PET/CT within a 7-day interval. Bone metastases were confirmed by follow-up using PET/CT, enhance-contrast computed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…99m Tc-MDP is widely used to detect bone metastases. However, sodium fluoride-18 (NaF) PET combined with CT (NaF-PET/CT) has a higher sensitivity and specificity (42, 43). NaF-PET/CT ensures quick, bone-specific, blood clearance and efficient visualization of the axial skeleton.…”
Section: Overview Of Pca Imaging Methodsmentioning
confidence: 99%
“…99m Tc-MDP is widely used to detect bone metastases. However, sodium fluoride-18 (NaF) PET combined with CT (NaF-PET/CT) has a higher sensitivity and specificity (42, 43). NaF-PET/CT ensures quick, bone-specific, blood clearance and efficient visualization of the axial skeleton.…”
Section: Overview Of Pca Imaging Methodsmentioning
confidence: 99%
“…Zhang et al retrospectively analyzed 45 patients with pathologically proven NPC. The sensitivity, specificity, and agreement rate of 18 F-NaF PET/CT for detecting metastatic bone lesions were 98.3%, 65.7%, and 92.9%, respectively, and concluded that 18 F-NaF PET/CT outperforms 18 F-FDG PET/CT [ 18 ]. Also, the sensitivity and accuracy of 18 F-NaF PET/CT in this study are in line with the previous study [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…For detecting skull-base invasion, 18 F-NaF PET/CT had a sensitivity, specificity, accuracy, positive predictive value, and negative predictive value of 100%, 94.7%, 97.8%, 96.3%, and 100%, respectively, whereas for 18 F-FDG PET/CT these measures were 65.4%, 100%, 80%, 100%, and 67.9%, respectively. The sensitivity and specificity for detecting bone metastatic lesions were 98.3%, and 65.7%, respectively, for 18 F-NaF PET/CT and 42.9%, and 97.1%, respectively, for 18 F-FDG PET/CT (Table 2) (62).…”
Section: F-naf Versus F-fdgmentioning
confidence: 99%